Peer Effects in Science: Evidence from the Dismissal of Scientists in Nazi Germany - Fabian Waldinger (Verein für Socialpolitik, 2010)
I investigate whether faculty quality and department size affect the productivity of scientists. The endogeneity problems related to estimating these effects are addressed by using the dismissal of science professors by the Nazi government as a source of exogenous variation. While local faculty quality is very important for PhD student outcomes it does not affect the productivity of professors. Local department attributes are thus much more important for young researchers who do not yet belong to a professional network outside their university. While not affected by the local department, professors' productivity is strongly affected by a high quality co-author network.
Keywords: I21; I28; J44; 330